(untitled) (Research, Society and Development, 2020)
The quilombola communities are living spaces where socioeconomic and cultural relations come together to constitute the local arrangement. This study aimed to analyze the social, economic, and cultural context of the Custaneira / Tronco quilombola community, located in the semi-arid region of Piauí, between the municipalities of Paquetá and Santa Cruz do Piauí. Participatory and non-participant observation were used as methodological procedures followed by the application of semi-structured forms to 144 residents. As support tools, voice recorder and field journal were used. The data reveal low levels of education and a predominance of females and married marital status. Regarding the age group, most are adults between 25 and 59 years old, earn less than one legal minimum wage, have lived in the community for more than 30 years and live in their own home, with masonry structure, tile covering and cement floor. They are mostly rural workers whose production is almost always for their own consumption. Corn (Zeamays L.), bean (Phaseolusvulgaris L.), and cassava (Manihotesculenta Crantz) are the main crops produced. The analysis shows that culture has a strong influence on the construction of the local arrangement, as well as a significant capacity for resilience and effective participation of residents in local decisions.